Diarrhea management in children under five in sub-Saharan Africa: does the source of care matter? A Countdown analysis. (December 2016) - Carvajal-Vélez, Liliana; Amouzou, Agbessi; Perin, Jamie; Maïga, Abdoulaye; Tarekegn, Hayalnesh; Akinyemi, Akanni; Shiferaw, Solomon; Young, Mark; Bryce, Jennifer; Newby, Holly
Abstract Background Diarrhea remains a high burden disease, responsible for nine percent of deaths in children under five globally. We analyzed diarrhea management practices in young children and their association with the source of care. Methods We used Demographic and Health Survey data from 12 countries in sub-Saharan Africa with high burdens of childhood diarrhea. We classified the quality of diarrhea management practices as good, fair, or poor based on mothers' reports for children with diarrhea, using WHO/UNICEF recommendations for appropriate treatment. We described the prevalence of diarrhea management by type and assessed the association between good management and source of care, adjusting for potential confounders. Results Prevalence of good diarrhea management is low in 11 of the 12 analyzed surveys, varying from 17 % in Cote d'Ivoire to 38 % in Niger. The exception is Sierra Leone, where prevalence of good practice is 67 %. Prevalence of good management was low even among children taken to health facilities [median 52 %, range: 34–64 %]. Diarrhea careseeking from health facilities or community providers was associated with higher odds of good management than care from traditional/informal sources or no care. Careseeking from facilities did not result systematically in a higher likelihood of good diarrhea management than care from community providers. The odds of good diarrhea management were similar for community versus facility providers in six countries, higher in community than facility providers in two countries, and higher in facility than in community providers in four countries. Conclusion Many children's lives can be saved with correct management of childhood diarrhea. Too many children are not receiving adequate care for diarrhea in high-burden sub-Saharan African countries, even among those seen in health facilities. Redoubling efforts to increase careseeking and improve quality of care for childhood diarrhea in both health facilities and at community level is an urgent priority.